The Effectiveness of Three Preservatives and the Relative Resistance of Ten Malaysian H:ardwoods against the Subterranean Termite, Coptoterm1es curvignathus (Holm.). - Sajap, Ahmad Said; Mohamad, Rosli; Abu Samah, Abd Rahim (1982)
Effectiveness of three preservatives and relative resistance of ten species of hardwoods were tested against the subterranean termite, Coptotermes curvignathus (Holm.), in laboratory bioassay. All three preservatives evaluated significantly increased wood resistance to attack. Copper-chrome-arsenic (CCA) was more effective than either sodium pentachlorophenol (Na PCP) or sodium tribromophenol (Na TBP). The bioassay indicated that the heavy hardwoods, Chengal and Resak were the least susceptible woods with a wood mass loss less than one per cent. The light hardwoods, Light red meranti, Jelutong andDamar minyak, were the most susceptible wood with a wood mass loss exceeding ten per cent.